"How does physical examination findings influence physiotherapists' decision-making when matching treatment to patients with low back pain?". (June 2021) - Widerström, Birgitta; Elvén, Maria; Rasmussen-Barr, Eva; Boström, Carina
Abstract : Background: Further clinical data how low-back pain (LBP) symptoms and signs manifests in physiotherapy clinical reasoning and treatment decision-making is needed. Objective: The aim was to explore and describe how symptoms and signs portrayed in three case descriptions of LBP influences physiotherapy treatment decision-making. Design: This was an exploratory interview study using inductive content analysis. Method: Fifteen semi-structured individual interviews were used to collect data of physiotherapists' treatment decision-making regrading three diverse LBP case descriptions. The participants were men, women, experienced and novice, working in primary healthcare settings in one sparsely populated region and in one larger city in Sweden. Findings: Two overarching themes were identified influencing decision-making for the treatment of LBP:1) Explicit assessment features distinguish treatment approaches; with categories describing how symptoms and signs were used to target treatment (nature of pain induce reflections on plausible cause; narrative details trigger attention and establishes knowledge-enhancing foci; pain-movement-relationship is essential; diverse emphasis of pain modulation and targeted treatment approaches): and 2) Preconceived notion of treatment, with categories describing personal treatment rationales, unrelated to the presented symptoms and signs (passive treatment avoidance and motor control exercise ambiguity). Conclusion: This study identifies how assessment details lead to decisions on diverse treatment approaches for LBP, but also that treatment decisions can be based on preconceived beliefs unrelated to the clinical presentation. The results underpin the mix of knowledge sources that clinicians need to balance and the necessity of self-awareness of preconceptions for informed and meaningful clinical decision-making. Highlights: Assessment findings used in physiotherapy decision-making in LBP were explored. Details in patient narrative and assessment establish targeted treatment approaches. The information source mixture in physiotherapy clinical reasoning is underscored. Personal convictions about treatments guided some decisions. Awareness of personal pre-conceptions is necessary for thoughtful decision-making.